IMPLEMENTATION OF PRINCIPLES OF RESTORATIVE JUSTICE IN CRIMINAL PROCEDURAL LEGAL PROCEEDINGS - Wijayanto, Candra; Hasuri (Universitas Bengkulu, 2024)
This study aims to assess and analyze how the principle of restorative justice is applied in criminal procedural legal proceedings. Normative juridical methods were used in the study. The results showed that, despite some obstacles and difficulties, the principles of restorative justice have been used in criminal procedural legal proceedings. In some situations, several key principles have been applied, such as recovery for victims, active participation of perpetrators in the recovery process, and community involvement in peacekeeping. Nevertheless, the concept of restorative justice is still a complex concept to understand and study, as well as the availability of adequate resources to support its implementation. This study improves our understanding of the use of restorative justice in criminal procedural law. This research can serve as a basis for making more efficient legal policies and practices that support restorative justice in enforcement. Keywords: Principles of Justice, Restorative Justice, Criminal Procedural Law.